Establishment and experimental verification of stability evaluation model for SBS modified asphalt: Based on quantitative analysis of microstructure. (30th January 2017) - Yin, Wei; Ye, Fen; Lu, Hang
Highlights: A novel stability evaluation model of SBS modified asphalt was proposed. The model considers both vertical and horizontal separation of two phases. The model was verified with regular softening point test. A relationship between micro and macro storage stability index was established. Abstract: This paper establishes a new model to evaluate the stability of SBS modified asphalt based on quantitative analysis of microstructure. The model considers both the vertical separation level and horizontal separation level, making it a more comprehensive one. The comprehensive evaluation index ϕ T, t in the model can better describe the influence of temperature and time on stability of SBS modified asphalt. At the temperature of 30 °C, 60 °C, and 120 °C, ϕ T, t shows a relationship with time which agrees with the logistic curve. The regular macro stability test was also carried out to verify the accuracy of the model. The curves of Softening Point Difference vs. time derived by the proposed model show a satisfactory agreement with the experiment-based curves, which proves the accuracy of the new model and the relationship between micro and macro stability index as well.